2019
DOI: 10.22219/jpbi.v5i3.9694
|View full text |Cite
|
Sign up to set email alerts
|

Augmented reality to facilitate students’ biology mastering concepts and digital literacy

Abstract: As one of abstract concepts, nervous system requires proper media which can represent the real condition. The purpose of this study was to observe the effect of augmented reality (AR) on students' mastering concept and digital literacy in biology. This quasi-experimental research was designed using non-equivalent control group design in which the instruments were test and questionnaire. The data were analyzed using independent samples t-test. The results indicated that AR gave significant positive effect on st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Application design is designed using Augmented Reality technology as part of a form of review of the learning material being taught. Provide clearer and more detailed information and use games as part of learning (Nurhasanah et al, 2019).…”
Section: Previous Researchmentioning
confidence: 99%
“…Application design is designed using Augmented Reality technology as part of a form of review of the learning material being taught. Provide clearer and more detailed information and use games as part of learning (Nurhasanah et al, 2019).…”
Section: Previous Researchmentioning
confidence: 99%
“…Through AR, learning has been brought to a new dimension because learners can easily visualize what is happening and understand complex concepts. Another study by Nurhasanah et al (2019) showed that AR can positively impact students' understanding of science concepts. Based on the results of data analysis using a non-equivalent control group design, it show differences between classes that use AR media and classes that do not use AR media in the science learning process.…”
Section: A Introductionmentioning
confidence: 99%
“…A lot of biology learning materials are abstract and difficult to understand due to the complexity of life concepts, especially if the learning content is microscopic or not available for direct observation (Chang, Chung and Huang, 2016;Nurhasanah, Widodo and Riandi, 2019;Wang et al, 2022). Therefore, digital visualization technologies have become essential for biology education since special equipment (such as high-tech microscopes) is often not affordable for educational institutions (Erbas and Demirer, 2019;Jenkinson, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Using mobile devices to integrate AR content in in-person or remote educational settings is more accessible and less expensive than with other types of AR hardware (such as smart glasses, headsets, AR projection systems, etc.) since most students already have appropriate smartphones (Nurhasanah, Widodo and Riandi, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation